Factors affecting upper airway control of NSAID‐exacerbated respiratory disease: A real‐world study of 167 patients - Annina Lyly; Anu Laulajainen‐Hongisto; Heikki Turpeinen; Seija I. Vento; Jyri Myller; Jura Numminen; Saara Sillanpää; Johanna Sahlman; Paula Kauppi; Sanna Toppila‐Salmi (Immunity, Inflammation and Disease)
Abstract Background Nonsteroidal anti‐inflammatory drug (NSAID) exacerbated respiratory disease (N‐ERD) is a triad with asthma, chronic rhinosinusitis with nasal polyps, and NSAID intolerance. Uncontrolled N‐ERD forms a major public health problem due to frequent and difficult‐to‐treat exacerbations and/or requiring putatively frequent endoscopic sinus surgeries (ESS). Our aim was to study factors affecting control of N‐ERD. Methods Retrospective patient record data (patient characteristics, prior sinus surgeries, follow‐up data in 2020) from 167 N‐ERD patients undergoing consultation at three tertiary hospitals from 2001 to 2017 was used. Outcome measurements reflecting uncontrolled N‐ERD were revision ESS, corticosteroids/biological therapy, and antibiotic courses during 2016–2020. Associations were analyzed by using nonparametric tests, Cox's proportional hazard, and binary logistic regression models. Results Nasal polyp eosinophilia increased the risk of revision surgery during the follow‐up (adjusted hazard ratio [aHR] 3.21, confidence interval 1.23–8.38). Also baseline oral corticosteroids (OCS; HR, 1.73, 1.04–2.89) and baseline surgery without total ethmoidectomy increased the risk of revision ESS (HR, 2.17, 1.07–4.42) in unadjusted models. In addition, both baseline OCS (adjusted odds ratio [aOR] 2.78, 1.23–6.26) and a history of ≥4 previous ESS (aOR, 2.15, 0.98–4.70) were associated with the use of OCS/biological therapy during the follow‐up, but not with high number of antibiotics. Conclusions Nasal polyp eosinophilia, baseline OCS, and a history of recurrent ESS predict uncontrolled N‐ERD. These factors might be clinically useful in risk‐estimation of uncontrolled disease and for organizing follow‐ups. Prospective cohort studies with larger sample size are needed to further study the factors affecting the upper airway control of N‐ERD.